In vitro and in vivo analysis of Clostridium perfringens supernatant isolates from alpaca enterotoxemia cases - Pérez J., David (2012)
In the present study, 24 native supernatants isolated from enterotoxemia fatalities were evaluated to characterize lecitinase, hemolytic, in vitro cytotoxicity, and in vivo enterotoxicity activities of the phospholipase C (Cp-PLC) exotoxin. The lecitinase activity was monitored in microplates using egg white emulsifications, the hemolityc and perfringolisine in microplates using sheep and equine eritrocytes respectively, the cytotoxic activity was tested on HEp-2 cells and the enterotoxicity by inoculating within intestinal loops of rabbits. At the molecular level, all the isolates (12 vegetative and 12 sporulated) were found to contain the cpa gene (genotype A), while six also contained cpb2 gene but none had the cpe gene. These isolates were classified, according the lecitinase activity, as high, medium and low producer strains. Most of the vegetative (66.6%) isolates had high and medium Cp-PLC production profiles, whereas all of the sprorulated ones were low producers. All high lecitinase production strains were citotoxic to HeP2 cells and the highest hemolytic activities (24.0 ± 8.4 u.a.h). Although the 66.6% (n=16) of the isolates induced intestinal fluid accumulations (0.12-0.47 mL/cm) none of the 24 isolates was able to produce intestinal lesions similar to enterotoxemia. The native supernantants showed presence of other toxins with hemolytic, citotoxic and enterotoxin activities similar to the Cp-PLC, CPE and â2 toxin that warrant further investigation to elucidate their possible role in the etiopathogenecity of enterotoxemia in alpacas.